Examining the Effects of Work Discipline and Employee Loyalty on Employee Performance: A Quantitative Study in Indonesia - Padlan Syafrin Azwir; Rahmi Syahriza; Nurbaiti Nurbaiti (Dinar : Jurnal Ekonomi dan Keuangan Islam, 2026)
This study aims to examine the effects of work discipline and employee loyalty on employee performance at PT Media Swara Prima Rantau Prapat. The study employs a quantitative approach with a causal associative research design. The population consists of all employees of the company, totaling 36 individuals. Data were collected through questionnaire distribution. Data analysis techniques include validity and reliability tests, classical assumption tests, and multiple linear regression analysis. Hypothesis testing was conducted using the t-test (partial), F-test (simultaneous), and coefficient of determination (R²).The results indicate that work discipline has a positive and significant effect on employee performance. Employee loyalty also shows a positive and significant effect on employee performance. Simultaneously, work discipline and employee loyalty have a positive and significant impact on employee performance. The coefficient of determination reveals that these two variables explain 59.6% of the variance in employee performance, while the remaining proportion is influenced by other variables outside the research model.These findings highlight the important role of work discipline and employee loyalty in improving employee performance at PT Media Swara Prima Rantau Prapat.